PENGARUH PENGGUNAAN MEDIA ALPHABET CARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SD N JATI I TAHUN PELAJARAN 2025 / 2026 - Apriliana Wulandari; Elinda Rizkasari; Dite Hastini (STKIP Subang, 2026)
Apriliana Wulandari. THE EFFECT OF ALPHABET CARD MEDIA USE ON BEGINNING READING ABILITY IN GRADE I OF SD N JATI I IN THE ACADEMIC YEAR OF 2025/2026. Thesis. Surakarta: Faculty of Teacher Training and Education, Slamet Riyadi University, Surakarta. January 2025. The purpose of this study focuses on whether there is an effect of using alphabet card learning media on the beginning reading ability of grade I at SD N Jati I Sumberlawang in the academic year of 2025/2026. The method used is a quantitative method using a Quasi Experimental Design research design in the form of Pretest-Posttest Control Group Design. The total number of grade I students at SD N Jati I Sumberlawang in the academic year of 2026 became the sample in this study. The sampling method used is total sampling, with 27 grade I students as participants. The data collection process uses observation, documentation, and testing methods. The results of the study showed that the hypothesis test results with a calculated t value of 5.115. The t table value at 26 degrees of freedom (i.e., 27-1) and a significance level of 5% was 2.056. The normality test results showed that the calculated t value (5.115) exceeded the t table value (2.056), so Ha was accepted and Ho was rejected. This study found that there was an increase in the average student learning from 64.21 (at the initial stage) to 81.89 (at the final stage). Thus, it can be concluded that the alphabet card learning media has an effect on the beginning reading skills of first-grade students at SD N Jati I Sumberlawang in the 2025/2026 academic year.